The development of the ‘self-directed learning readiness scale in biology’ (SDLRSbio) for pre-university biology students - Siew Wai, K.; Daniel, E.G.S. (2013)
In past research, the measurement of students’ SDL readiness focused on self-motivation, self-management, and self-monitoring. These measurements were found to be too general to conclude one as a self-directed learner. Self-directedness should be specific for each subject area. This paper will discuss the pilot study of a larger research, where the SDLRSbio was developed using the Delphi technique. Specific biology laboratory skills readiness, experimental skills readiness, and data analysis and interpretation skills readiness were embedded in the SDLRSbio to ensure specificity in measuring biology students’ SDL readiness. The SDLRSbio developed consisted of 46 items in a 5 point Likert-scale. This scale was pilot tested with 30 students in Kuala Lumpur. The total scores were superimposed on a readiness continuum to reflect students’ SDL readiness. The Cronbach-alpha reading for the 46 items was 0.869. Results showed that, 73% of the biology students in the pilot study were moderately ready for SDL. 17% was less ready for SDL, and 10% was ready for SDL. This result has implications for planning and developing curricula of biology related fields.